2002
DOI: 10.1021/cm010758x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Study of the Decomposition of Dimethyl Methylphosphonate (DMMP) on Metal Oxides at Room Temperature and Above

Abstract: The adsorption and decomposition reactions of dimethyl methylphosphonate (DMMP) on a commercial γ-Al 2 O 3 , a γ-Al 2 O 3 -supported iron oxide, and a sol-gel-prepared alumina have been examined at temperatures from 25 to 400 °C. The capacities of these solids for the decomposition of DMMP have been measured, and the identities and amounts of the decomposition products determined over the entire temperature range. The alumina surfaces yield higher total amounts of decomposition products than the supported iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(103 citation statements)
references
References 19 publications
6
96
0
1
Order By: Relevance
“…The base line recovery for SMO sensors after the exposure to DMMP is very poor which limits its long time applicability. In an attempt to understand the reasoning behind this significant reduction in the sensors response, metal oxide nanopowders including WO 3 were fabricated in previous work [39,[58][59][60]. The surface behavior towards DMMP vapor was studied at various temperatures.…”
Section: Page 11 Of 38mentioning
confidence: 99%
“…The base line recovery for SMO sensors after the exposure to DMMP is very poor which limits its long time applicability. In an attempt to understand the reasoning behind this significant reduction in the sensors response, metal oxide nanopowders including WO 3 were fabricated in previous work [39,[58][59][60]. The surface behavior towards DMMP vapor was studied at various temperatures.…”
Section: Page 11 Of 38mentioning
confidence: 99%
“…Several studies have been conducted in order to investigate the effects of temperature conditions on adsorption and decomposition of DMMP on TiO 2 surface [11][12][13][14][15][16]. Rusu and Yates [15] reported that at the temperature lower than −113 • C, DMMP condenses as an ice layer on the outer surface of TiO 2 .…”
Section: Photocatalytic Decomposition Of Gaseous Dmmp By Tiomentioning
confidence: 99%
“…Above −59 • C (from −59 • C to 213 • C), cleavage of P-OCH 3 groups takes place, with the production of Ti-OCH 3 species, and the dissociation of chemisorbed DMMP is seen. Sheinker and Mitchell [16] reported on the thermal decomposition of DMMP on ␥-Al 2 O 3 at temperatures from 25 • C to 400 • C and showed that the DMMP that is adsorbed is decomposed at 25 • C and increasing temperature brings about an increase in the decomposition activity of the surface. In our study, the temperature of the interior reactor was controlled as one of the optimization processes, in order to prevent DMMP adsorption as far as possible.…”
Section: Photocatalytic Decomposition Of Gaseous Dmmp By Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the electronic environment on the surface also changes prompting surface chemistry to change. These intriguing properties along with chemical functionalities promote enhanced decontamination properties towards environmental contaminants [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%